An Extraordinary Pardon - Langhauser, Derek (Maine Policy Review, 2024)
The author of this commentary describes the theory, origin, purpose, and process of the pardon power generally. He then discusses the story behind the pardon of Donald Gellers by Maine Governor Janet T. Mills. And finally, the author explains how this pardon helped advance subsequent policy actions in Maine.